Effect of single clove garlic on clinical symptoms of photoaging in wistar rats exposed with UV-B - Nyoman Pratiwi Hapsari Dewi; I Gusti Ayu Dewi Ratnayanti; I Gusti Kamasan Nyoman Arijana; Ni Made Linawati (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Background: Photoaging is a premature aging that occurs on skin due to the ultraviolet light exposure that causes the emergence of clinical symptoms, one of which is wrinkle. One kind of material that can prevent photoaging is antioxidant. A single clove garlic has the highest antioxidant activity compared to the other materials. Aim: This research aimed at investigating the effectivity of single clove garlic in inhibiting the clinical symptom of photoaging. Method: This research was an experimental research, utilizing pre-post-test control group design. The used sample were 30 male wistar rats which were divided into 6 experimental groups. All groups were exposed to UV-B light with the amount of 840 mJ/cm2. Control group (P1) was only exposed to UV-B while the other groups were treated with placebo cream (P2), sunblock (P3), 5% garlic cream (P4), 10% garlic cream (P5) and 20% garlic cream (P6) respectively. The clinical symptom in the form of wrinkle was observed by using dermascope and the observations were categorized based on Glogau Scale. The statistical analysis utilized Wilcoxon and Kruskal Wallis test which was followed by Mann Whitney test. Result: The result of the research showed that there was significant difference on the apparent wrinkle on P1 group and P3, P5 and P6. Meanwhile the comparison between P1, P2 and P4 was not significant. Conclusion: The single clove garlic extract can prevent photoaging and has the similar protective effect for the skin as of sunblock.